2019
DOI: 10.1080/14767058.2019.1667323
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen treatment after the first days of life in preterm neonates with patent ductus arteriosus

Abstract: Aim: Patent ductus arteriosus (PDA) is treated with ibuprofen and it is known that the clearance of ibuprofen increases with postnatal age. We aimed to study whether postnatal age-adjusted ibuprofen dosages improve the effectiveness of treatment compared to standard ibuprofen dosages after the first days of life. Methods: A historical cohort of 207 preterm neonates treated with standard ibuprofen dosages (Group A; 2011-2015) was compared to a prospective cohort of 66 preterm neonates treated with postnatal age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…As spontaneous ductus closure increases with PNA, part of ductus closure reported in prophylactic and early treatment studies may be due to spontaneous closure rather than drug treatment. Efficacy of PDA pharmacotherapy seems to decrease, with post-natal age, even if dosages are increased with PNA to correct for increased clearance with age (10,13). This suggests either a certain window of opportunity for PDA treatment during the physiological process that is involved in the spontaneous closure of the ductus arteriosus or the need for higher drug exposures at older ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As spontaneous ductus closure increases with PNA, part of ductus closure reported in prophylactic and early treatment studies may be due to spontaneous closure rather than drug treatment. Efficacy of PDA pharmacotherapy seems to decrease, with post-natal age, even if dosages are increased with PNA to correct for increased clearance with age (10,13). This suggests either a certain window of opportunity for PDA treatment during the physiological process that is involved in the spontaneous closure of the ductus arteriosus or the need for higher drug exposures at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, early treatment strategy may be favored because the pharmacological closure rate seems to be highest on the 1st days of life (11,12). Despite the limited studies on delayed treatment with NSAIDs and paracetamol, this late treatment seems less effective (13,14). NSAIDs and paracetamol may enhance the spontaneous closure process.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] In a study on the efficacy of ibuprofen in the treatment of PDA, ibuprofen showed results as effective as indomethacin, but with fewer adverse events, because it has less effect on cerebral, kidney, and mesenteric blood flow than indomethacin. [35,36] However, side effects of COX inhibitors are inevitable, and administration of 3 doses of ibuprofen can increase the risk of IVH. In such cases, it may be difficult to distinguish whether the occurrence of IVH is due to the PDA or ibuprofen administration.…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, the Z ‐score for birthweight ( Z Birthweight‐for‐GA ) was calculated based on birthweight, GA, and Dutch perinatal growth curves 10 . The cohort has been previously described by de Klerk et al 11 …”
Section: Methodsmentioning
confidence: 99%
“…For each patient, the Zscore for birthweight (Z Birthweight-for-GA ) was calculated based on birthweight, GA, and Dutch perinatal growth curves. 10 The cohort has been previously described by de Klerk et al 11 Ibuprofen exposure and concentrations A previously developed population PK model for ibuprofen in preterm infants 8 was used to calculate ibuprofen exposure upon the applied dosing strategies based on relevant patient characteristics. For oral administrations, 100% bioavailability was assumed and the absorption rate constant was set at 0.6562 hour −1 .…”
Section: Patients and Datamentioning
confidence: 99%